Awareness of child abuse and neglect among teachers of urban and rural schools – A comparative study - Zeba Kaunain; Swarna Swathi Silla; Sampath Reddy Cheruku; Ziauddin Mohammad; Sarada Penmetcha; Prathap Chandar Manivannan (Journal of Family Medicine and Primary Care)
Context: Child abuse and neglect (CAN) remains a pressing issue worldwide, with teachers often being the first to notice signs of abuse in children. This study aims to compare the knowledge, attitudes, and practices (KAP) regarding CAN among primary school teachers in urban and rural areas of Telangana, India. Aim: The primary aim of this study is to assess and compare the KAP among teachers from both rural and urban schools about CAN. Methodology: A cross-sectional study involving 400 primary school teachers (200 urban, 200 rural) were selected through stratified random sampling. An 18-question survey assessed demographics and KAP related to CAN. Data were analyzed using SPSS 25.0, with Chi-square tests. Results: The awareness, attitudes, and practices of primary school teachers regarding CAN reveal stark differences between urban and rural settings. Urban teachers demonstrated statistically significant higher levels of knowledge and attitude in handling CAN issues compared to their rural counterparts. Conclusion: The study calls for quality-focused standardized training to enhance teachers’ confidence and knowledge about CAN, regardless of geographic location. Collaborative efforts to integrate the best practices into teacher education are essential to improve the handling of child abuse cases and ensure the protection of vulnerable children. Clinical Significance: This study underscores the critical need for improved and standardized training for teachers to effectively handle CAN and highlights the importance of establishing robust support systems to encourage reporting and ensure the protection of children. CTRI NO.: CTRI/2023/11/060167